Critical education in the Irish repeal movement. Issue 2 (3rd July 2022) - Fitzsimons, Camilla
Abstract: This article is written from a pro-choice perspective. Through a radical, inclusive feminist lens, I examine educational aspects of the Irish repeal movement; a 35 year long, grassroots movement that forced the hand of reluctant politicians into calling a referendum to repeal the eighth amendment. I draw from websites and media interviews, my own experience as an academic-activist, and aspects of comprehensive mixed methods research I carried out over a three-year period (2018–2021). I maintain it was the independent (non-state funded) nature of pro-choice groups that enabled them to determine their own structures and tactics including participative, dialogic, hands-on, adult education. As the Irish reproductive rights movement enters a new phase of seeking to improve one of Europe's most conservative laws, I argue for a reproductive justice approach that expands its demands far beyond the single issue of abortion access. An ongoing critical pedagogic dimension is crucial as part of this struggle.